2008
DOI: 10.1007/s00167-008-0612-0
|View full text |Cite
|
Sign up to set email alerts
|

The fate of patellar tendon and infrapatellar fat pad after arthroscopy via central portal

Abstract: Central patellar (CP) portal is an accessory portal in arthroscopic knee surgery, which generally is considered to be safe. In this cross sectional study, we aimed to delineate the clinical and radiological outcome of patellar tendon (PT) and Hoffa's fat pad after the use of this approach. From our hospital records, patients who underwent arthroscopy via CP portal were identified and were invited for the study. There were16 men and 4 women with a mean age of 32 years. Mean follow-up time was 28 months. Menisce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 17 publications
0
28
3
1
Order By: Relevance
“…15,16,21 Other tendinopathic-like features such as mild degenerative changes, 18 increase in cellularity and vascularity, 17 hypoechogeneity, and hyperechogeneity, 15,20,21 increase in tendon width 15,[17][18][19][20]21 as observed with MRI and ultrasonography have also been reported. Bayar et al 15 further described their patients having changes similar to tendinopathy in 6 out of 20 patients. This suggested that acute injury as created by the removal of the central one-third of patellar tendon could develop tendinopathic-like changes.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…15,16,21 Other tendinopathic-like features such as mild degenerative changes, 18 increase in cellularity and vascularity, 17 hypoechogeneity, and hyperechogeneity, 15,20,21 increase in tendon width 15,[17][18][19][20]21 as observed with MRI and ultrasonography have also been reported. Bayar et al 15 further described their patients having changes similar to tendinopathy in 6 out of 20 patients. This suggested that acute injury as created by the removal of the central one-third of patellar tendon could develop tendinopathic-like changes.…”
mentioning
confidence: 90%
“…[8][9][10][11][12] Clinical studies have occasionally reported ectopic calcification after Achilles tendon rupture 13,14 as well as calcification and tendinopathic-like changes in patellar tendon donor site after anterior cruciate ligament (ACL) reconstruction. [15][16][17][18][19][20][21] We hypothesized that chondro-osteogenesis and change in the ECM composition of the repair tissue after acute tendon injury might contribute to the poor tissue quality. This study therefore aimed to examine the presence of chondrocyte phenotype and ossification inside the window wound of the patellar tendon.…”
mentioning
confidence: 99%
“…3,5,7,8,12,21,28 The precise cause of CaDs in tendons remains unknown. 9 CaDs in the patellar tendon have been found in volleyball 21 and basketball athletes, 5 as well as in postsurgical patients.…”
mentioning
confidence: 99%
“…9 CaDs in the patellar tendon have been found in volleyball 21 and basketball athletes, 5 as well as in postsurgical patients. 3,12,28 …”
mentioning
confidence: 99%
“…We thank Dr Checa for this important contribution and comments on our article [1], although these two studies are different in terms of methodology.…”
mentioning
confidence: 99%